Security and Privacy in Wireless and Mobile Networks - Georgios Kambourakis (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Currently, at the dawn of 5G networks, and the era of the Internet-of-Things, wireless and mobile networking is becoming increasingly ubiquitous. In this landscape, security and privacy turn into decisive factors. That is, the mobile and wireless ecosystem is an ideal playground for many perpetrators: (a) handheld devices are used for critical tasks, such as e-commerce, bank transactions, payments, application purchases, as well as social interaction; (b) such devices uniquely identify their users and store sensitive and detailed information about them; and (c) despite all their sophistication, native security mechanisms of mobile operating systems can be bypassed, and several wireless interfaces and protocols have been proven to be vulnerable to attack. As the attacker is given so many alternative entry points for penetration, the creation of assaults against the end-user and the underlying systems and services have been augmented, both in amount, as well as in matters of complexity. It is, therefore, imperative that new and advanced security and privacy-preserving measures are deployed. To cope with the aforementioned challenges, this edited book has been dedicated to the security and privacy aspects of mobile networks, wireless communications, and their apps. Particularly, apart from network and link layer security, the focus is on the security and privacy of mobile software platforms and the increasingly differing spectrum of mobile or wireless apps. This edited book presents a collection of nine chapters. All the chapters constitute original research work addressing a variety of topics pertaining to the above-mentioned challenges.